Radiopacity and flow of different endodontic sealers - Tanomaru Filho, Mario [UNESP]; Bosso, Roberta [UNESP]; Viapiana, Raqueli [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (My University, 2013)
The present study evaluated the radiopacity and flow of different endodontic sealers: AH Plus, Endo CPM, MTA Fillapex, Sealapex, Epiphany, and Epiphany SE. For the radiopacity test, six specimens measuring 10mm in diameter and 1mm in thickness were fabricated from each material. They were radiographed on an occlusal film alongside an aluminum step wedge. Radiographs were digitized to determine the radiopacity equivalence in millimeters of aluminum. To evaluate the flow, a 120 g load was placed on top of a glass slab containing 0.05 } 0.005ml of sealer. The diameters of each material were measured (mm) with a caliper and samples were photographed. Digitized images were analyzed using the UTHSCSA Image Tool for Windows software, to determine the sealer area (mm2). Data were submitted to ANOVA and Tukey's test at 5% significance. AH Plus and Epiphany SE presented the greatest radiopacity (12.5 mm Al and 12.0 mm Al, respectively) (p>0.05), followed by Epiphany (9.6 mm Al) and Fillapex (8.9 mm Al). Endo CPM (5.46 mm Al) and Sealapex (5.51 mm Al) presented lower radiopacity. MTA Fillapex presented significantly higher values of flow than other sealers (33.11 mm and 844.9 mm2). AH Plus, Epiphany, and Epiphany SE had similar values. Endo CPM (21.05 mm and 342.8 mm2) and Sealapex (19.98 mm and 352.5 mm2) presented the lowest flow values (p>0.05). All sealers presented radiopacity and flow values according to ISO and ANSI/ADA recommendations.

O objetivo deste estudo foi avaliar a radiopacidade e o escoamento dos cimentos endodonticos: AH Plus, Endo CPM Sealer, Fillapex, Sealapex, Epiphany e Epiphany SE. Para o teste de radiopacidade foram confeccionados corpos de prova com 10mm de largura e 1mm de espessura, radiografados juntamente com uma escala de aluminio sobre filme oclusal. As imagens foram digitalizadas e foi determinada a equivalencia em milimetros de aluminio. Para avaliacao do escoamento, foram colocados 0,05 } 0,005 ml do cimento em placa de vidro, e sobre este uma massa de 120g. Foi realizada mensuracao do maior e menor diametro de cada especime e as amostras foram fotografadas e digitalizadas para mensuracao da area do cimento em mm2 pelo programa UTHSCSA Image Tool for Windows Versao 3.00. Os dados foram analisados por ANOVA e teste Tukey, com 5% de significancia. AH Plus e Epiphany SE apresentaram maior radiopacidade (12,5 mm Al e 12,0 mm Al, respectivamente) (p>0,05), seguidos pelo Epiphany (9,6 mm Al) e Fillapex (8,9 mm Al). Endo CPM (5,46 mm Al) e Sealapex (5,51 mm Al) apresentaram menor radiopacidade. O MTA Fillapex apresentou valor de escoamento superior aos demais materiais (33,11 mm e 844,9 mm2). Os cimentos AH Plus, Epiphany e Epiphany SE apresentaram valores similares e intermediarios (p>0,05), seguidos pelos cimentos Endo CPM Sealer (342,8 mm2 e 21,05 mm) e Sealapex (352,5 mm2 e 19,98 mm) que apresentaram menor escoamento (p>0,05). Todos os cimentos avaliados estao em acordo com as recomendacoes da norma ISO e ANSI/ADA.
Radiopacidade e escoamento dos cimentos endodónticos ah plus, endo CMP sealer, MTA fillapex, sealapex, epiphany e epiphany se
Keywords: Endodontic sealers; Radiopacity; Flow; Mineral trioxide aggregate; Cimento endodontico; Radiopacidade; Escoamento; Mineral Trioxido Agregado